The Wilderness Trail - Bedford-Jones, H. (Henry), 1887-1949 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Wilderness Trail" by H. Bedford-Jones is a historical novel written in the early 20th century. Set in the tumultuous early 19th-century American frontier, the narrative follows the experiences of John Norton as he navigates both interpersonal conflicts and the broader tensions of a society marked by lawlessness, political strife, and frontier struggles. Central to the story is the iconic figure of Colonel Daniel Boone, as well as a cast of characters that include lawyers, settlers, and indigenous peoples, all woven into a tale of adventure and intrigue. The opening of the book introduces us to a vibrant landscape characterized by the tumult of American post-independence society, focusing on a fateful encounter between John Norton and Colonel Boone on a Kentucky road. Tensions simmer as Norton's chance meeting with a lawyer named Charles Duval provokes hostility, setting the stage for further conflict. As the plot unfolds, Norton learns of various dangers, including river pirates that threaten trade and travel, while also making connections with Boone and the lively frontier community. The stage is set for a journey filled with danger, unexpected alliances, and the quest for justice on the wild frontier. (This is an automatically generated summary.)
Release date is 2022-02-16
Al Haines
Keywords: United States -- History -- 19th century -- Fiction